Edukasi Pengenalan Penggolongan Obat pada Siswa SDN 1 Dono Tulungagung - Sulastri, Sulastri; Kumalasari, Nurul Chamidah; Santoso, Arif; Nurjannah, Mutia Hariani (Universitas Pahlawan Tuanku Tambusai, 2025)
Classifying drugs according to the labeling on the drug packaging is very important because it functions to ensure that the drugs to be consumed by someone are safe and effective in producing therapeutic effects. The problem faced by students of SDN 1 Dono is that they still do not fully understand drug classification. The methods used were lectures, distribution of leaflets and questionnaires, and conducting questions and answers with students. The purpose of the counseling is to improve the safety and effectiveness of drug use, as well as ensure proper drug distribution. This activity began with providing drug introduction education to students of SDN 1 Dono about the importance of drug classification based on the labeling on the drug packaging. The results of the activity were approximately 85% (26 students) gained increased knowledge about drug classification. The conclusion of the educational counseling activity on drug classification introduction at SDN 1 Dono was proven effective in increasing students' knowledge about drug classification.